Efficiency and Effectiveness of Mandatory Spending in Regional Education Expenditure: A Case Study of Central Java Province (2019-2022) - Eva Putri Larasati; Yuwita Ariessa Pravasanti; Suprihati Suprihati (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the efficiency and effectiveness of the use of mandatory spending in the management of regional expenditure in the education sector in 35 districts/cities in Central Java Province for the 2019–2022 fiscal year. Mandatory spending is an obligation to allocate at least 20% of the APBD for education, as regulated in national regulations. Efficiency is measured by the Data Envelope Analysis (DEA) method using an output-oriented approach and Variable Return to Scale (VRS) assumptions, where an area is said to be efficient if its efficiency score = 1. Meanwhile, effectiveness is assessed based on the comparison of output and outcomes, and is said to be effective when it reaches a percentage of 90–100%. The results show that there is a disparity between regions. Only Klaten Regency and Semarang City have shown perfect efficiency for four consecutive years. However, none of the areas achieved perfect effectiveness throughout the study period. The COVID-19 pandemic has also affected the dynamics of education budget realization, which has an impact on achieving efficiency and effectiveness. These findings provide strategic implications for local governments in developing education budget policies that are more optimal and oriented towards improving the quality of human resources.